Attitudes and expectations of gastroenterology outpatients about the importance of diet and possible relationship to their symptoms. Issue 4 (13th July 2012) - Adesokan, Akintayo; Neild, Penny
Abstract : Objectives: To evaluate gastroenterology outpatients' attitudes to the importance of diet and its relationship to their symptoms, as well as their expectations of dietary advice from health professionals. Design: Prospective clinical audit. Setting: Gastroenterology outpatient department of St George's Healthcare NHS Trust. Patients: Two hundred and twenty-five patients, aged between 18 and 70 years met the inclusion criteria. Interventions: None. Main outcome measures: Participants' responses to a structured questionnaire. Results: Sixty-nine per cent of participants felt their diet played an important role in their condition. Factors significantly associated with a positive dietary attitude included younger age (40.6 years vs 46.0 years, p<0.01), regularity of dietary pattern (108 vs 35, p<0.01), number of symptoms (4.6 vs 2.5, p<0.01), severity of gastrointestinal symptoms (2.3 vs 1.5, p<0.01), history of weight loss (34% vs 20.3%, p<0.05) and history of dietary advice (71.1% vs 33.3%, p<0.01). Sixty-eight per cent (68%) of participants were interested in receiving dietary advice, though only 36% expected to receive it. No differences were found for any comparisons based on average body mass index. Conclusion: The majority of gastroenterology outpatients view diet as playing an important role in their condition, particularly those who have more severe symptoms and those who have received dietary advice. Although a large proportion of patients are interested in receiving dietary advice, few expect to receive it in clinics. Further research is required to explore the reasons why, and to assess the confidence of health professionals in providing nutritional advice.